2017
DOI: 10.1111/ijac.12674
|View full text |Cite
|
Sign up to set email alerts
|

A computational and experimental study on the effective properties of Al2O3‐Ni composites

Abstract: It has been demonstrated that effective medium approximation and mean field homogenization technique is a useful computational tool to predict the effective thermal and structural properties of alumina‐nickel (Al2O3‐Ni) composites. Nickel particle size and volume fraction, thermal interface resistance and porosity are found significant factors that affect thermal conductivity, elastoplastic behavior, elastic modulus and thermal expansion coefficient of Al2O3‐Ni composite. To complement the computational design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…elastic modulus and coefficient of thermal expansion (cte). Akhtar et al 3 have found a good agreement between the experimentally measured CTE and the one predicted by mean-field homogenization of Mori-Tanaka as outlined by Benveniste and Dvorak 28 . According to the mean-field homogenization scheme the effective properties are estimated using the Eqs.…”
Section: The Scheme For the Computational Design Of Composite Materialssupporting
confidence: 55%
See 2 more Smart Citations
“…elastic modulus and coefficient of thermal expansion (cte). Akhtar et al 3 have found a good agreement between the experimentally measured CTE and the one predicted by mean-field homogenization of Mori-Tanaka as outlined by Benveniste and Dvorak 28 . According to the mean-field homogenization scheme the effective properties are estimated using the Eqs.…”
Section: The Scheme For the Computational Design Of Composite Materialssupporting
confidence: 55%
“…According to the mean-field homogenization scheme the effective properties are estimated using the Eqs. (1) to (3). C eff and α eff are the homogenized stiffness tensor and the effective CTE of the resulting composite, respectively whereas C and α represent stiffness tensors and CTE, respectively…”
Section: The Scheme For the Computational Design Of Composite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are always large differences in the thermal expansion coefficients between metal phase and ceramic phase, which also easily leads to a poor bonding at the phase interfaces during the heating and cooling process [154][155][156][157]. For example, Lu et al [158] observed holes in the two-phase interface of sintered A1 2 O 3 /nickel (Ni) cermet due to the different thermal expansion coefficients of Ni and A1 2 O 3 , which could reduce the interface bonding force and adversely affected the mechanical properties of the cermet. Moreover, chemical reactions are easy to occur in the interface of solid and liquid phases during the preparation process.…”
Section: Main Factors For Interface Bondingmentioning
confidence: 99%
“…that can lead to achieve the expected structural and thermal properties. Akhtar et al , for example, have reported a design scheme for composite materials. Using the predictions of appropriate properties estimation models, they estimated the required particle size and volume fraction of filler for reaching a targeted set of structural and thermal properties.…”
Section: Introductionmentioning
confidence: 99%